Revistas - Telos, Publicación (Telos: Revista de Estudios Interdisciplinarios en Ciencias Sociales, 2024)
Eileen J. Findlav Portable Roots: Latin New Yorker Community Building and the Meanings of Women’s Return Migration in San Juan. Puerto Rico, 1960-2000